Porous Functionalized Covalent-Triazine Frameworks for Enhanced Adsorption Toward Polysulfides in Li-S Batteries and Organic Dyes - Qianhui Liu; Shuhao Yang; Hlib Repich; Yixuan Zhai; Xiaosa Xu; Yeru Liang; Hejun Li; Hongqiang Wang; Fei Xu (Frontiers in Chemistry, 2020)
The incorporation of functional building blocks to construct functionalized and highly porous covalent triazine frameworks (CTFs) is essential to the emerging adsorptive-involved field. Herein, a series of amide functionalized CTFs (CTF-PO71) have been synthesized using a bottom-up strategy in which pigment PO71 with an amide group is employed as a monomer under ionothermal conditions with ZnCl2 as the solvent and catalyst. The pore structure can be controlled by the amount of ZnCl2 to monomer ratio. Benefitting from the highly porous structure and amide functionalities, CTF-PO71, as a sulfur cathode host, simultaneously demonstrates physical confinement and chemical anchoring of sulfur species, thus leading to superior capacity, cycling stability, and rate capability in comparison to unfunctionalized CTF. Meanwhile, as an adsorbent of organic dye molecules, CTF-PO71 was demonstrated to exhibit strong chemical interactions with dye molecules, facilitating adsorption kinetics and thereby promoting the adsorption rate and capacity. Furthermore, the dynamic adsorption experiments of organic dyes from solutions showed selectivity/priority of CTF-PO71s for specific dye molecules.